IMPLEMENTASI CLOUD COMPUTING TECHNOLOGY UNTUK SMK PGRI 2 TANGERANG BERBASIS GAFE (GOOGLE APPS FOR EDUCATION) - Ari Asmawati; Ria Dwi I’zzaty; Tasya Oktavianti (UNIVERSITAS RAHARJA, 2019)
Technological developments that are so very fast, require that every individual or institution follow suit. Like the use of clud computing, the usage is currently very wide. In the world of education, the use of cloud computing is very useful for teachers and students in terms of learning in class and outside the classroom. Application of Gafe stored in the cloud provides many choices of office, chat and other applications. This system will try to be implemented in Tangerang PGRI 2 SMK, which is currently still using a manual system. This system allows teachers and students to communicate with each other and interact with each other.